Environmental risks of trace elements associated with long-term phosphate fertilizers applications: A review - Jiao, Wentao; Chen, Weiping; Chang, Andrew C.; Page, Albert L. (Environmental pollution (1987), 2012)
Application of phosphate fertilizer can be a significant contributor of potentially hazardous trace elements such as arsenic, cadmium, and lead in croplands. These trace elements have the potential to accumulate in soils and be transferred through the food chain. We articulated the environmental risks of trace elements associated with long-term phosphate fertilizer applications by combining data from the literature and results from model simulations. Results illustrate that under normal cropping practice, the impact of phosphate fertilizers applications on trace element accumulation in receiving soils has been limited and localized. Their plant uptake varied greatly depending on the fertilizer application rates, soil and plant characteristics. This has led to a great deal of uncertainty in characterizing soil distribution coefficients, Kd, and plant uptake factors, PUF, two of the most used parameters in assessing the risks of accumulations. Therefore, the risks may be more appropriately assessed based on the probabilistic distributions of Kd and PUF. Environmental risks of trace elements associated with long-term phosphate fertilizer applications were articulated by combining data from the literature and results from model simulations.